2020
DOI: 10.31893/jabb.20039
|View full text |Cite
|
Sign up to set email alerts
|

Neurobehavioral and neuroprotector effects of caffeine in animal models

Abstract: This review aims to analyze and contrast the neurological effects associated with the use of caffeine on neurobehavior and neuroprotection in animal models. Caffeine belongs to the group of methylxanthines that exert a direct effect on adenosine receptors associated with inhibitory or excitatory G proteins, generating modification of cyclic AMP activity and intracellular calcium flow which produces alterations in the modulation system of the neurotransmitters dopamine and glutamate. The regulation of the neuro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 72 publications
0
12
0
Order By: Relevance
“…While many studies suggest that caffeine produces improvement in memory either in animal (Munawar, 2022;Villanueva-Garcia et al, 2020) or in human (Borota et al, 2014;Sherman et al, 2016;Hartney, 2020) models of learning and memory, other studies report that caffeine does not affect memory (Nehlig, 2010) or even its craving impairs memory (Palmer et al, 2017). Some studies reported that long-term consumption of caffeine could inhibit hippocampus-dependent learning and memory partially through inhibition of hippocampal neurogenesis (Han et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…While many studies suggest that caffeine produces improvement in memory either in animal (Munawar, 2022;Villanueva-Garcia et al, 2020) or in human (Borota et al, 2014;Sherman et al, 2016;Hartney, 2020) models of learning and memory, other studies report that caffeine does not affect memory (Nehlig, 2010) or even its craving impairs memory (Palmer et al, 2017). Some studies reported that long-term consumption of caffeine could inhibit hippocampus-dependent learning and memory partially through inhibition of hippocampal neurogenesis (Han et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…The use of animal models has significantly contributed to the understanding of perinatal asphyxia. Several studies have used animal models for the induction of fetal asphyxia, including maternal hypoxemia, infrared thermography (IRT), reduction of in uteroplacental blood flow, umbilical cord occlusion, and embolization, among others [ 46 , 47 , 48 , 51 , 92 , 147 , 148 , 149 , 150 , 151 , 152 , 153 ] ( Figure 3 and Figure 9 ). Infrared thermography (IRT) is a technique used in both veterinary and human medicine to quantify the surface temperature of the skin based on visualizations of thermographic changes [ 154 ].…”
Section: Animal Models Of Perinatal Asphyxiamentioning
confidence: 99%
“…Caffeine has neuroprotector and cytoprotector effects in cases of dopamine-induced damage by regulating the levels of this neurotransmitter [29]. Caffeine has also been associated with an effect that retards signs of neuronal degeneration in diseases like Parkinson's and Alzheimer's, effects that occur through interaction with adenosine receptors and a possible association with N-methyl D-aspartate receptors (NMDA), which increase cognition and delay the onset of the associated signs [35][36][37].…”
Section: Studies On the Neuroprotective Activity Of Newly Synthesized...mentioning
confidence: 99%